Differential Effectiveness of Differentiated Learning Strategies in the Merdeka Curriculum: A Comparative Study with the 2013 Curriculum: no thanks - Mochamad Muchson; Zainal Afandi; Sugiono Sugiono (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This study examines the effect of differentiated learning strategies implemented in the Merdeka Curriculum compared to the 2013 Curriculum on student learning outcomes. Methodology: Using a quantitative comparative design, data were collected from report card scores of 36 students (20 from the Merdeka Curriculum and 16 from the 2013 Curriculum) and analyzed using an independent sample t-test. Main Findings: Findings reveal a significant improvement in learning outcomes for students under the Merdeka Curriculum (M=79.95) compared to the 2013 Curriculum (M=77.40), with a mean difference of 2.55 (p < 0.05). Novelty/Originality of this study: This research highlights the effectiveness of differentiation in Indonesian curriculum reform and provides evidence for policymakers to adopt student-centered strategies to enhance learning outcomes.